Judges’ Legal Reasoning in Determining the Success or Failure of Diversion in Juvenile Justice: A Normative Analysis of Indonesian Court Decisions - Dahlan, Anwar; Bima, Muhammad Rinaldy; Djanggih, Hardianto (Al-Ishlah: Jurnal Ilmiah Hukum, 2025)
This study examines judges’ legal reasoning in determining the success or failure of diversion in juvenile cases within Indonesia’s Juvenile Criminal Justice System. Using a normative juridical approach with a doctrinal character, the research analyzes statutory provisions under Law Number 11 of 2012 and selected district court decisions that reflect diverse diversion outcomes. The findings reveal that although diversion is an imperative legal mandate, its implementation varies significantly in judicial practice. Diversion may succeed substantively when judges actively facilitate restorative dialogue and involve probation officers effectively, but it may fail when reduced to procedural formality or financial compensation negotiations. The study also identifies instances where diversion is entirely omitted despite meeting normative requirements, reflecting a persistent retributive bias in juvenile adjudication. These inconsistencies demonstrate that diversion outcomes are strongly influenced by judicial discretion, victim willingness, socio-economic factors, and the availability of non-material restoration mechanisms. The study concludes that diversion must be reinforced as a substantive right of the child rather than a mere administrative obligation. Strengthening judicial guidelines, enhancing probation services, and promoting restorative justice-oriented judicial training are essential to ensure consistent, child-centered, and restorative diversion practices